2013
DOI: 10.1111/jcmm.12035
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of sema3a in myocardial infarction border zone decreases vulnerability of ventricular tachycardia post‐myocardial infarction in rats

Abstract: The expression of the chemorepellent Sema3a is inversely related to sympathetic innervation. We investigated whether overexpression of Sema3a in the myocardial infarction (MI) border zone could attenuate sympathetic hyper-innervation and decrease the vulnerability to malignant ventricular tachyarrhythmia (VT) in rats. Survived MI rats were randomized to phosphate buffered saline (PBS, n = 12); mock lentivirus (MLV, n = 13) and lentivirus-mediated overexpression of Sema3a (SLV, n = 13) groups. Sham-operated rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…28 Chen and colleagues have shown that overexpression of sema3A in MI border zone could reduce the inducibility of ventricular arrhythmias by reducing sympathetic hyper-innervation after infarction. 32 These results demonstrate that NGF-induced augmentation of sympathetic nerve sprouting in diseased hearts leads to lethal arrhythmias and SCD.…”
Section: Pathophysiologymentioning
confidence: 77%
“…28 Chen and colleagues have shown that overexpression of sema3A in MI border zone could reduce the inducibility of ventricular arrhythmias by reducing sympathetic hyper-innervation after infarction. 32 These results demonstrate that NGF-induced augmentation of sympathetic nerve sprouting in diseased hearts leads to lethal arrhythmias and SCD.…”
Section: Pathophysiologymentioning
confidence: 77%
“…These Sema3a transgenic animals display spontaneous premature ventricular contractions and an increased susceptibility to ventricular arrhythmias (Ieda et al, 2007). Recently, Chen et al (2013) reported that overexpression of Sema3a in border zone myocardium surrounding a recent myocardial infarction can reduce hyper-innervation that normally accompanies the response to injury, consequently reducing susceptibility to ventricular tachycardia.…”
Section: Pulmonary Vein Patterningmentioning
confidence: 99%
“…Cardiac-specific overexpression of Sema3a induces a reduction of sympathetic innervation and transgenic animals display susceptibility to ventricular tachycardia 44 . Accordingly, it has been reported that myocardial overexpression of Sema3a 45 or intravenous administration of recombinant Sema3A protein 46 after infarction in rats can reduce the probability of ventricular tachycardia that frequently is an associated response to injury, as a result of attenuated sympathetic reinnervation. Moreover, a nonsynonymous polymorphism (I334V, rs138694505A>G) in exon 10 of the human SEMA3A gene was associated with unexplained cardiac arrest and ventricular fibrillation; the axon repelling activity SEMA3A I334V appears significantly weaker of that of its wild type counterpart and in the hearts of patients sympathetic nerves invade the subendocardial layer 47 …”
Section: Sema3amentioning
confidence: 99%